Impacts of Commuting Practices on Social Sustainability and Sustainable Mobility - Melina Stein (Sustainability, 2022)
Commuting is an integral part of many people’s everyday life providing a transition between private and working life. It does, however, lead to negative impacts at a personal and social-ecological level (health impacts, lack of time, climate emissions, etc.). This article is based on the transdisciplinary research project “CommuterLab” (PendelLabor), which investigates commuting practices in the German Rhine-Main region. Using a practice-theoretical approach, we conducted a qualitative empirical study to explore how commuters organise the transition between their personal life and job. Through our analysis, we were able to identify different meanings of commuting and its strong interconnection with other everyday practices. This allowed us to gain deep insight into the social (non-)sustainability of commuting. At the core of our results are four different types of commuting practice whose impact on social sustainability differs widely. Furthermore, since the interviews were conducted during the coronavirus pandemic, respondents had their first experience of strongly reduced commuting. This in turn allowed insights into the changing organisation of everyday life and the impact of reconfigured commuting practices on social sustainability. Based on these results, we drew conclusions about the dynamics of commuting in terms of social sustainability.